Natural nest sites of the European Starling Sturnus vulgaris in a primeval temperate forest. Issue 2 (3rd April 2021) - Wesołowski, Tomasz
ABSTRACT : Capsule: European Starlings Sturnus vulgaris nested mostly in natural holes with strong walls (in live trees), typically excavated by medium-sized woodpeckers (small entrances, deep cavities), and high above the ground. Co-occurrence of these safety-enhancing features suggests that predation avoidance has been the main force shaping patterns of Starling nest site selection. Aims: To describe patterns of nest site use by Starlings in a primeval forest and to assess the adaptive value of nest site choice. Methods: Observations were made of Starlings breeding in undisturbed conditions in a strictly protected part of the Białowieża National Park, Poland. Intensive searches were made for nests ( n = 2039) in permanent observation plots during 46 breeding seasons (1975–2020), coupled with measurements of hole attributes and observations of fate and re-use of nest sites. Results: Starlings bred along forest edges in holes located in several species of deciduous tree; tree species used differed among habitats and hole location differed across tree species. The birds bred mostly in holes excavated by woodpeckers (70.3%), in trunks (77.4%) of living trees (84.5%). The median girth at breast height of these trees amounted to approximately 170 cm and median height of holes above the ground was 13 m. Starlings used holes excavated by the medium-sized woodpeckers roughly in proportion to their availability in the forest (tree species, stature, height above the ground). About 39% of holes were re-used in the consecutive years, with some holes being used over several decades. Conclusion: The features of Starling nest holes (strong walls, narrow entrances, deep cavities) probably constitute adaptations to the need to evade predators. Their body size allows them to nest in excavated holes without threat of their broods being destroyed by woodpeckers.